Originally Posted by
Bruce Elimination means you eliminate either the x term or the y to term to leave you with just y = or x =.
As there are 2 xs in both terms, we can subtract the second term from the first to eliminate the xs.
$\displaystyle 2x  2y = 61$

$\displaystyle 2x + y = 7$
=
$\displaystyle 3y = 68$
$\displaystyle y = 22.666...$
Now that you have y, all you need to do is solve the first equation using y as 68.
So $\displaystyle 2x  2 * 22.6666... = 61$
$\displaystyle 2x = 106.3333...$
$\displaystyle x = 53.1666...$
Very odd answers, but that is correct. The above poster is incorrect as he mistook 2x  2y = 61 to be 2x + 2y = 61.